IDENTITY CHARACTERISTICS OF TEACHERS IN THE FINAL YEARS OF ELEMENTARY EDUCATION RELATED TO THE SCHOOL CONTEXT - Freire, Mirela Leão; Gama, Maria Eliza Rosa (Seven Editora, 2025)
This research is part of the Graduate Program in Public Policy and Educational Management at the Federal University of Santa Maria and is an excerpt from the master's dissertation: "Implications of the School Context on the Professional Identity of Final Grade Elementary School Teachers at a School in Santa Maria, RS." The study of teacher identity is not new; however, in recent decades, with the transformations we see in our society, it has presented new paradigms. This article aims to understand how teachers define/characterize the identity aspects of their professional work collective and what identity characteristics they attribute to their work at the school studied. This is a qualitative study, in which narrative interviews were conducted, addressing teachers' perceptions of their professional identity and how the school environment relates to the development of their teaching work. The data sources for the research are the teachers of the Arco-íris school, five elementary school teachers. The results of this research highlight the complexity of teaching in socially vulnerable contexts, where teachers act beyond simply transmitting content and are agents of acceptance and transformation. Teaching identity is marked by empathy, adaptability, and ethical commitment. Completing this research was more than an academic exercise; it was an act of listening, recognition, and commitment to teaching in its most human form.DOI: https://doi.org/10.56238/sevened2025.038-023